Analisis Saluran Pemasaran dan Margin Pemasaran Daun Tunas Air Tembakau di Desa Kilensari Kecamatan Panarukan Kabupaten Situbondo - Mayangsari, Andina; Mikala, Kawakibi Ahmad Fadhil (Universitas Galuh, 2025)
The aim of this research is to determine the type of tobacco marketing channel and the size of the marketing margin in each channel. The snowball sampling method was used in this research to find a series of tobacco marketing channels from farmers to final consumers. This method is used because it allows researchers to find a series of tobacco marketing channels from farmers to final consumers. The research results show that there are two tobacco marketing channels in Kliensari Village, Panarukan District. One Level Marketing Channel has a marketing margin of IDR. 17,000/kg and the Two Level Marketing Channel has a marketing margin of IDR. 46.365/kg /kg.